2012
DOI: 10.1002/jmv.23410
|View full text |Cite
|
Sign up to set email alerts
|

Influence of B cells in liver fibrosis associated with hepatitis B virus harboring basal core promoter mutations

Abstract: The development of the liver disease in chronic hepatitis B with common viral variants can be determined through the interaction between the virus and the host immune response. B cells constitute half of the intrahepatic lymphocyte population with an impact on fibrosis. A proliferation-inducing ligand (APRIL) has been shown to have a co-stimulatory activity on B cells. For this study HBV DNA was amplified and then sequenced to show the presence of the basal core promoter (BCP) mutations in the serum from 57 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…The percent of CD19 + CD3 − B cells in CHB patients was significantly higher than those in HD, consistent with recent data on chronic HCV infection. 31 B cells play a decisive role in fibrosis and later stages of liver disease, 32 though we did not find a significant difference in liver fibrosis stages.…”
Section: Discussioncontrasting
confidence: 85%
“…The percent of CD19 + CD3 − B cells in CHB patients was significantly higher than those in HD, consistent with recent data on chronic HCV infection. 31 B cells play a decisive role in fibrosis and later stages of liver disease, 32 though we did not find a significant difference in liver fibrosis stages.…”
Section: Discussioncontrasting
confidence: 85%
“…Moreover, it has been shown that the activation of B-cells, in a T-cell independent pathway, produced immunoglobulins and cytokines in the liver that changed fibrotic responses [11, 16]. Our recent study showed the association of IgD positive B-cells with the fibrosis stage in chronic hepatitis B [17]. The intrahepatic lymphocytes are recognized as long-lived recirculating B-cells and are similar to splenic B2 cells that produce cytokines IL-2, IL-4, TNF α , and IL-6 with proinflammatory function and contribute to disease pathogenesis in an antibody-independent fashion, perhaps by modulating T cell responses [16, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Principally, the stop codon mutation at base 1896 creates the truncated precore peptide that might represents an adaptation to immune pressure [30]. The function of innate immune response as the first line of defense against virus infection as well as its cooperation with adaptive immunity may induce the development of precore mutant variants of HBV [11, 31, 32]. Therefore, the clinical significance of these mutations appears to be linked to the function of host immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of innate immunity in liver damage also has been identified in several studies [10, 11]. Toll-like receptors (TLRs) describe a group of pattern recognition receptors (PRRs) playing critical roles in the host innate immune response [12].…”
Section: Introductionmentioning
confidence: 99%